IPTEK BAGI MASYARAKAT MESIN PERONTOK PADI DI DESA BANYU ASIN - Pristiansyah Pristiansyah; Hasdiansah Hasdiansah; Muhammad Haritsah Amrullah (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2022)
Rice is one of the basic foodstuffs consumed by the people of Indonesia as well as Bangka Belitung Islands Province more precisely Bangka Regency Riau Silip Village Banyu Asin. Freshly harvested rice is usually still not separated from straw / malai. The process of harvesting rice still uses traditional tools or also called gebotan. The threshing machine available in Banyu Asin has not been able to maximize the results of the platform, which resulted in the length of the threshing process. Based on these needs, it was designed to build a rice threshing machine to facilitate the threshing process. Rice threshing machine design refers to the VDI 2222 method of development which has 4 (four) stages, namely: planning, conceptualizing, designing, and finishing, then assessed based on technical, and economic aspects. The conclusion obtained during the design process of the rice threshing machine is the design of the machine weighing 60 kg lighter than the existing machine is easy to move and the design of the machine whose components are easy to remove installs. The design of a rice threshing machine that is able to knock rice as much as 86.4kg / hour, compared to existing machines is only able to knock rice as much as 30kg / hour.